Globalization, Governmentality and Global Politics - LIPSCHUTZ, Ronnie D. (Routledge, 2005)
Globalization, Governmentality and Global Politics details how the widespread failure of states and corporations to regulate the impact of increased globalization has given rise to non-governmental organizations and movements, aiming to influence corporations regarding social responsibilities and address key issues such as human rights, environmental destruction, unhealthy working conditions and child labour.